2016
DOI: 10.7763/ijiet.2016.v6.779
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Project-Based Learning on Learning Motivation and Problem-Solving Ability of Vocational High School Students

Abstract: Abstract-Due to pay too much attention to pencil-and-paper test, lacking of learning motivation and problem-solving ability are quite popular for the vocational high school students in Taiwan. This study developed a project-based curriculum for the vocational high school students majored in food and beverage, and examine the effect of the curriculum on students' learning motivation and ability of problem solving by means of quasi-experimental method and qualitative analysis. The objects of this study are the s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

12
186
2
40

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 278 publications
(240 citation statements)
references
References 10 publications
12
186
2
40
Order By: Relevance
“…The activity begins with a fundamental question about waste problems. This is in accordance with research by Chiang and Lee (2016), the results showed that project-based learning not only improved vocational school students' learning motivation, but facilitated their problem-solving abilities. In the design activities of a plan for the project students discuss to determine the waste management project and then consult with the lecturer.…”
Section: Figure 2 Discuss Identifying Packaging Markssupporting
confidence: 91%
“…The activity begins with a fundamental question about waste problems. This is in accordance with research by Chiang and Lee (2016), the results showed that project-based learning not only improved vocational school students' learning motivation, but facilitated their problem-solving abilities. In the design activities of a plan for the project students discuss to determine the waste management project and then consult with the lecturer.…”
Section: Figure 2 Discuss Identifying Packaging Markssupporting
confidence: 91%
“…Besides, motivation also contains a managerial implications which is associated with an individual's managerial activity to encourage someone to pursue particular objectives. Students' learning motivation can be stimulated by a learning model (Chiang & Lee, 2016). Cooperative learning model has been developed and confirmed as one learning model that can improve students' performance.…”
mentioning
confidence: 99%
“…The more positive response of students to learning after implementing the blended-PBL is in line with some of the previous reports. Some studies report that PBL is learning that can increase student motivation (Chiang & Lee, 2016), as well as in blended learning (Afip, 2014). Therefore, combining both of them could to increase student motivation.…”
Section: Resultsmentioning
confidence: 99%